Spatial conflict resolution in marine spatial plans and permitting procedures for offshore wind energy: an analysis of measures adopted in Denmark, England and the Netherlands - Juul E. H. Kusters; Ferry M. G. van Kann; Christian Zuidema (Frontiers in Marine Science)
As activities in the North Sea are steadily increasing in both size and number, spatial conflicts are becoming increasingly inevitable. Marine Spatial Planning is widely adopted as an area-based planning approach to manage competing claims for maritime space, but spatial conflicts are also managed through permitting procedures for maritime activities. To explore how Denmark, England and the Netherlands resolve, minimize or mitigate spatial conflicts, this paper identifies what conflict resolution measures are adopted in marine spatial plans and permitting procedures, and analyzes how national institutional capacities shape their deployment. Collected data includes marine spatial plans and permitting documents as well as interviews with involved policy- and decision-makers. The findings demonstrate a common set of guiding principles for conflict resolution in their marine spatial plans across countries, including spatial reservation, multi- or co-use, ecosystem-based planning, and financial compensation. Within permitting procedures, a wide variety of spatial, physical-technical, logistic, and financial conflict resolution measures are adopted to minimize or mitigate spatial conflicts on project-specific levels. However, large differences exist in the degree to which decision-makers prescribe what conflicts must be addressed in what manner during project development. A lack of ecological and spatial knowledge and fragmented governmental responsibilities hinder decision-makers’ freedom to deviate from established types of conflict resolution measures. Overall, this paper presents valuable insights on how conflicts are addressed across the North Sea region as well as how institutional capacities, and institutional space in particular, shape the adoption of conflict resolution measures.